Age- and Gender-Specific Unemployment and Okun's Law in CEE Countries. Issue 4 (4th July 2017) - Dunsch, Sophie
Abstract : Unemployment rates, especially youth unemployment rates, have increased in various countries of Europe over the last years. This article examines age- and gender-specific unemployment rates in Central and Eastern European countries by using Okun's law. It tests the hypothesis that young people are more vulnerable to business cycle fluctuations. Gender- and age-specific Okun coefficients for ten different countries plus the EU-15 are estimated. The results show that young people in the CEE countries are predominantly more sensitive to business cycle fluctuations, independent of gender.